Challenges of Those in Leadership in The Digitalisation of Nigeria’s Government Organisations - Ugochukwu D. Abasilim; John O Durojaiye; Daniel E. Gberevbie (Universitas Medan Area, 2022)
It is becoming increasingly difficult to function without using information and communication technology in all areas of human endeavour. This is because it promotes accountability and openness, which provides citizen-centred administration emphasising easier access to better delivery of government services. Digitalisation is one of the techniques available to government organisations to improve the effectiveness and efficiency of delivering services to the public. This is predicated on the notion that efficient digitalisation of the day-to-day activities of government processes will result in the provision of adequate services to citizens. However, there are various obstacles to effective digitalisation in government organisations in Nigeria. For instance, lack of information technology infrastructure, intermittent power/electricity supply, lack of trained and competent employees, a general aversion to change, etc. Of all the challenges aforementioned, the challenge of those in leadership stands out as a significant component that hinders digitalisation in government organisations in Nigeria. This paper examines the challenges of those in leadership in the digitalisation of Nigeria’s government organisations, as well as proposes suggestions on how to deal with the challenges. Data was gathered from secondary sources such as relevant books, journals and the internet. This paper finds out that the attitude and reluctance to change by leaders in government organisations restrict the adoption and successful digitalisation of their day-to-day activities, which negatively impacts the delivery of high-quality services to the citizens. This paper suggested that the requisite Information Communication Technology infrastructure for digitalisation should be provided by the Federal Government, as the majority of government organisations lack the fundamental infrastructure required to properly digitalise their operations. The government should develop ICT policies that make computer literacy a requirement for hiring and promotion of public or civil servants at all levels, including the federal, state, and local governments.